Generation Z's perception of brand activism - Semchuk, Anastasiia (2022)
This work was carried out to determine the impact of brand activism on the perception of the younger generation Z in the Czech Republic. A qualitative approach was used to conduct the analysis, which helped to analyze the collected data from in-depth interviews. This method helped to find out the opinion of people from the same age category in a particular country. The study proved that brand activism affects generation Z’s perception. The results showed that it is essential for the younger generation to see that brands are not silent and talk about the problems of society. It is crucial for them to understand that the company is making important steps towards a high-quality relationship to its consumers. It was also revealed that brand activism affects brand image. This phenomenon improves the brand in the eyes of the younger generation. In addition, brand activism can change customer characteristics. Generation Z will choose a brand that expresses its opinion about public issues. Overall, the results showed that Generation Z responds positively to brand activism.